2017
DOI: 10.1088/1361-648x/aa7b56
|View full text |Cite
|
Sign up to set email alerts
|

Phonon limited electronic transport in Pb

Abstract: We present a fully ab initio based scheme to compute electronic transport properties, i.e. the electrical conductivity σ and thermopower S, in the presence of electron-phonon interaction. We explicitly investigate the [Formula: see text] structure of the Éliashberg spectral function, the coupling strength, the linewidth and the relaxation time τ. We obtain a state-dependent τ and show its necessity to reproduce the increased thermopower for temperatures below the Debye temperature, without accounting for the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…2 and Eq. 4 is ensured by employing adaptive tetrahedron schemes 17,18,45 and using, depending on the topology of the iso-energetic surface, a few 10 4 (10 3 ) k-points and 10 5 (10 5 ) q-points for bulk and monolayer, respectively 8 . In Fig.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…2 and Eq. 4 is ensured by employing adaptive tetrahedron schemes 17,18,45 and using, depending on the topology of the iso-energetic surface, a few 10 4 (10 3 ) k-points and 10 5 (10 5 ) q-points for bulk and monolayer, respectively 8 . In Fig.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…Relativistic effects, e.g., spin-orbit coupling, were treated self-consistently and are accounted for in all calculations. Based on the electronic and vibrational properties, the el-ph coupling was obtained within a modified version of the EPW code [16,17], either for the freestanding SL WS 2 or for the states in the SL in the presence of the Au(111) substrate.…”
mentioning
confidence: 99%
“…( 1). Recent theoretical work on elemental metals showed that there exists a remarkable k dependence of τ even in such simple metals when the electron-phonon interaction is considered [48,49]. Because we do not know the precise representation of τ n (k), we cannot discuss the effect of (ii) quantitatively.…”
Section: B Magnetotransport Properties In the Normal Metallic Phase I...mentioning
confidence: 96%